Monitoring of human activities around the Asian elephant reserve based on NPP-VIIRS night light remote sensing images: A case study in Xishuangbanna, China - Zhao, Fei; Zhang, Yiyang; Zhao, Zhifang; Wang, Xinrui; Zhang, Sujin; Luan, Guize; Zhang, Qiting; Zhu, Ling; Liu, Hairong (Frontiers in Ecology and Evolution, 2023)
The Asian elephant (Elephas maximus) have a wide range of foraging needs and heterogeneous habitat preferences that bring them close to the forest edge. Currently, most of the range of wild elephants is located outside protected areas (PA). Nighttime light data (NTL) has been used as a component of human footprint due to its characteristics of characterizing the intensity of human activities and spatio-temporal continuity. We chose Xishuangbanna National Nature Reserve, the main distribution area of Asian elephants, as the study area and used NTL to monitor human activities, supplemented by land cover (LC) type data, to study the Asian elephant sanctuary and its surrounding areas, and found that: 1) NTL features inside and outside the PA are approaching, and the boundary effect of the sanctuary is weakening; 2) The NTL gathering area in the study area is mainly distributed in the south of the PA, 86.21% of the area’s nighttime lights have a significant increase trend, and the human activity range is evolving toward the southeast in the past decade; 3) the percentage of areas with a significant increasing trend of NTL under different LC types is greater than decreasing, nearly 50% of the forest showed an increasing trend of NTL. LC types with reduced forest have been converted to cropland and building in the last decade.